2015
DOI: 10.1021/ef502461s
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Maleic Acid and Aluminum Chloride Catalyzed Dehydration and Degradation of Glucose

Abstract: We report the positive effect of maleic acid, a dicarboxylic acid, on the selectivity of hexose dehydration to 5hydroxymethyfurfural (HMF) and subsequent hydrolysis to levulinic and formic acids. We also describe the kinetic analysis of a Lewis acid (AlCl 3 ) alone and in combination with HCl or maleic acid to catalyze the isomerization of glucose to fructose, dehydration of fructose to HMF, hydration of HMF to levulinic and formic acids, and degradation of these compounds to humins. The results show that AlCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
99
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 23 publications
5
99
0
1
Order By: Relevance
“…In-situ 27 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Based on the kinetics data, the k value and initial TOF of the AlCl3-catalyzed conversion of glucose were obtained (Table S1). 40 The k value increased with the increase of temperature and the concentration of AlCl3, and the initial TOF increased with increasing the temperature but decreased with increasing the concentration of AlCl3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In-situ 27 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Based on the kinetics data, the k value and initial TOF of the AlCl3-catalyzed conversion of glucose were obtained (Table S1). 40 The k value increased with the increase of temperature and the concentration of AlCl3, and the initial TOF increased with increasing the temperature but decreased with increasing the concentration of AlCl3.…”
Section: Methodsmentioning
confidence: 99%
“…In-situ27 Al NMR spectra of the reaction mixtures with time. Reaction conditions: 0.8 mL of the reaction mixtures (1.0 mL D2O, 0.25 M Glc, 25.0 mM AlCl3), 383 K.…”
mentioning
confidence: 99%
“…However, the successive use of homogeneous and heterogeneous Lewis acid catalysts has been effective for HMF production from glucose in water or an organic solvent. [13][14][15][16][17][18][19][20][21][22][23][24] Zhang and co-workers reported that CrCl 2 acts as an efficient catalyst for glucose conversion into HMF in an ionic liquid, where the HMF yield reached ca. 70% at 373 K. 13 In this catalytic system, the Lewis acid center of CrCl 2 plays a crucial role, especially in the rate-determining proton transfer of glucose into fructose.…”
mentioning
confidence: 99%
“…17,18 The best choice for the production of furan compounds is the use of a biphasic system that is formed by an aqueous phase (reaction solvent) and an organic phase (extraction solvent).…”
mentioning
confidence: 99%
“…5,[14][15][16] These systems avoid the main side-reactions in dehydration, such as rehydration to produce levulinic and formic acids and condensation of furan derivatives to produce a dark insoluble solid residue called humins. 17,18 The best choice for the production of furan compounds is the use of a biphasic system that is formed by an aqueous phase (reaction solvent) and an organic phase (extraction solvent). 19 This system must have a high partition coefficient for furan compounds and, in case of water miscible solvents such as THF, it is necessary to add an electrolyte to induce phase separation.…”
mentioning
confidence: 99%